การพัฒนาระบบกำกับติดตามสำหรับการพัฒนาครูด้วยระบบหนุนนำต่อเนื่อง - แต้วัฒนา ธนรัตน์; รุ่งเรือง กิตติคุณ; อินทรัศมี พัชนา (Journal of Research and Curriculum Development, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อพัฒนาระบบกำกับติดตามสำหรับการพัฒนาครูด้วยระบบหนุนนำต่อเนื่อง เพื่อเสริมสร้างผลสัมฤทธิ์ทางการเรียน และทักษะในศตวรรษที่ 21 ของนักเรียนจังหวัดนครนายก วิธีดำเนินการวิจัยแบ่งเป็น 5 ขั้นตอน ได้แก่ 1) ประชุมสนทนากลุ่มย่อยผู้เชี่ยวชาญเพื่อกำหนดรูปแบบของระบบการกำกับติดตาม 2) พัฒนาตัวบ่งชี้ด้วยวงจรคุณภาพ PDCA 3) จัดทำคู่มือระบบการกำกับติดตาม 4) ประชุมสนทนากลุ่มผู้เชี่ยวชาญเพื่อตรวจสอบความตรงเนื้อหา และ 5) ทดลองใช้และปรับปรุงระบบกำกับติดตาม กลุ่มตัวอย่างการวิจัยเป็นผู้บริหารโรงเรียน ศึกษานิเทศก์ และครูที่ทำหน้าที่เป็นโค้ชในโครงการวิจัยระบบหนุนนำต่อโรงเรียนในจังหวัดนครนายก จำนวน 15 คน จาก 15 โรงเรียน แบ่งเป็นระดับชั้นประถมศึกษา 9 โรงเรียน และ ระดับมัธยมศึกษา 6 โรงเรียน ผลการวิจัยพบว่า ระบบการกำกับติดตามใช้การประเมินแบบการให้คะแนนแบบแยกองค์ประกอบ (analytic scoring) และคะแนนของตัวบ่งชี้กำหนดเป็นรายข้อเรียงลำดับตามวงจร PDCA มีตัวบ่งชี้ทั้งหมด 8 ตัวบ่งชี้ แบ่งเป็น 2 ประเภท ได้แก่ ปัจจัยนำเข้า 2 ตัวบ่งชี้ และกระบวนการ 6 ตัวบ่งชี้ ได้แก่ 1) สรรถนะของครูผู้สอน 2) สภาพแวดล้อมที่ส่งเสริมการเรียนรู้ 3) องค์ประกอบของแผนกิจกรรมการเรียนรู้ตาม 3R3C 4) ความเป็นไปได้ของแผนกิจกรรมการเรียนรู้ตาม 3R3C 5) การนำแผนการเรียนรู้ไปปฏิบัติ 6) กระบวนการโค้ช 7) การสะท้อนความคิดให้ข้อมูลย้อนกลับ และ 8) การทบทวนปรับปรุงประสิทธิภาพของแผนการเรียนรู้ ระบบกำกับติดตามนี้จะได้ผลดีหากจัดให้มีแนวทางกำกับติดตามโดยเฉพาะการกำหนดบทบาทหน้าที่ให้ชัดเจน และปฏิบัติตามกระบวนการของการกำกับติดตามอย่างต่อเนื่อง Development of Monitoring System for the Teacher Coaching System The purpose of this study was to develop a monitoring system for teacherdevelopment by using the teacher coaching system for enhancing learning achievementsand the 21st century skills of Nokhonayok province students. The study involvedfive stages: 1) a panel of experts to determine a draft model of monitoring system,2) development of indicators by using the PDCA Cycle, 3) creation of a monitoringsystem manual, 4) seminar with the panel to validate the content and 5) implementationand improvement. The sample consisted of school administrators and teachers acting ascoaches from fifteen participant schools: nine primary schools and six secondaryschools.The findings show that: 1) the analytic scoring methods were used to evaluatethe developed monitoring system and 2) the scores of eight indicators determined fromthe items and based on the PDCA Cycle were classified into two types: one was twoinput indicators, while the other was six process indicators. These eight indicatorswere: 1) competency of school teachers, 2) environment for learning enhancement,3) elements of learning plans according to the 3R3C, 4) feasibility of the learning plans,5) implementation of the learning plans, 6) coaching process, 7) reflective thinking andfeedback, and 8) revision of the learning plans for greater efficiency. This developedmonitoring system would be more effective if the guidelines were properly promulgatedwith clearer roles of those involved and if the process of the monitoring system werefollowed accordingly on a continual basis.